(untitled) (Physical Education, Health and Social Sciences, 2026)
Synthetic dyes in industrial effluents pose a significant environmental and health problem worldwide. Acid Orange dyes, which are azo dyes, are the most persistent, toxic, and non-biologically degradable among them. They are released into water bodies uncontrollably, which decreases light penetration, interferes with photosynthesis, and alters aquatic biodiversity. Moreover, the decomposition products of azo dyes are usually mutagenic and carcinogenic, which makes the long-term health risks to humans and the environment a concern. Although these conventional dye treatment technologies, such as coagulation-flocculation, advanced oxidation, and membrane-based processes, have proven to be effective under controlled conditions, they are characterized by high operational costs, secondary sludge formation, and low efficiency in the treatment of dilute dye effluents. Another alternative adsorbent that has proven to be economical, sustainable, and environmentally friendly is biochar, which is a carbon-rich substance formed through the pyrolysis of agricultural residues. Quinoa (Chenopodium quinoa) residues, including husks and stems, are a new feedstock for biochar production, with distinct physicochemical characteristics, and can be valorized as a waste in a circular economy context. In addition, nanocomposites of quinoa biochar with nanomaterials have been synthesized by modifying biochar with nanomaterials, which have increased adsorption capacity, surface reactivity, and reusability. The mini review illuminates the use of quinoa biochar and its nanocomposites in the removal of Acid Orange dye in wastewater, the mechanisms of adsorption, their performance comparison, challenges, and future outlook.